A carbon composite sodium iron sulfate positive electrode material and its preparation method and application
Patent Information
- Application Number
- CN202410700523.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-05-31
AI Technical Summary
In the prior art, when preparing sodium iron sulfate positive electrode material, the particles appear loose in microscopic state, the contact is not tight enough, and it is difficult to achieve continuous scale production in the wet process.
By controlling the combination of wet mixing, suction filtration or press filtration, solid phase sintering, and controlling the median particle size of the slurry after sanding, the raw materials are mixed evenly to ensure high particle density.
The high compaction density of the cathode material is achieved, the electrochemical performance of the material is improved, and the problem of loose materials and difficulty in achieving continuous scale production in the prior art is overcome.
Smart Images

Figure CN118479548B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery material preparation, and specifically relates to a carbon composite sodium iron sulfate positive electrode material and a preparation method and application thereof. Background Art
[0002] Sodium batteries have become the most likely battery system to partially replace lithium batteries due to their low cost, high safety, and good low-temperature performance. The most critical part of the sodium battery system is the positive electrode material. Currently, sodium positive electrode materials are divided into three categories: layered oxides, polyanions, and Prussian blue. Layered oxides have high specific capacity and high compaction density, so the energy density of the battery system is high, but the material has complex structural phase changes under high charge state, and the whole battery system has gas production problems, which limits the cycle life. The Prussian blue system material has low cost, but the compaction density is the lowest, and the material has obvious defects in the molecular structure during the preparation process. Its three-dimensional open crystal structure is easy to store water molecules, so in the battery system, it will be released as the battery is charged and discharged, causing the electrolyte to decompose, greatly affecting the cycle life of the battery. The polyanion system has a very good cycle life, but the gram capacity is low and the compaction density is also low, so the battery cell specific energy is low. However, as a typical polyanion material, sodium iron sulfate has a high average voltage and low raw material cost, so the average cost per kilowatt-hour of the battery cell is very low and has good safety. However, sodium iron sulfate has poor intrinsic conductivity and low sintering temperature, making it difficult to achieve in-situ carbon coating. In order to improve its conductivity, non-in-situ carbon conductive agents such as conductive carbon (Super P), acetylene black, Ketjen black, and carbon nanotubes are generally added during the precursor mixing stage. Since the conductive carbon materials are relatively light and are all nanoparticles, there are problems with the uniformity of the mixing.
[0003] The raw materials for the synthesis of sodium ferric sulfate materials are generally sodium sulfate and ferrous sulfate. Sulfate materials generally have strong hygroscopicity, so contact with water should be avoided as much as possible during the synthesis process. Sodium ferric sulfate synthesis usually adopts low-temperature solid-phase sintering method, and the difficulty lies in the process of mixing raw materials in the precursor stage. Currently, the commonly used methods include dry method and wet method.
[0004] The dry process includes: 1) dry ball milling, which has the advantage of simple process, but has the problem of easily causing material agglomeration, wall adhesion, uneven mixing, difficulty in separating the ball and material, and low yield; 2) air flow milling mixing in an inert atmosphere, which has the advantage of effectively solving the problems of agglomeration, wall adhesion, and ball-material separation, and is easy to realize industrial mass production, but has the problem of this pneumatic mixing method easily causing uneven mixing of materials of different densities, and the mixed raw materials are relatively loose, and the contact between particles is poor at the microscopic level.
[0005] The wet process includes wet ball milling or sand milling. Considering the problem that ferrous sulfate materials are easy to absorb water, the liquid phase solvent used in the wet process is generally an organic solvent. The advantages of the wet process are higher mixing efficiency, good uniformity, and can greatly improve the problem of uneven dispersion of nano carbon sources. The prior art discloses a method for preparing sodium ferric sulfate, which first adopts wet ball milling, evaporates and then sintered at low temperature. This method has several defects, such as (1) the mixing process is carried out in a closed tank body, and each mixing requires the sealed tank body to be disassembled again, which is difficult to achieve continuous large-scale production; (2) the method of evaporating and removing the solvent does not consider the control of the organic solvent; (3) the precursor obtained by evaporation also has the problem that the particles are loose at the microscopic level and the contact between the particles is not close enough. In order to achieve continuous large-scale production, sand milling is a commonly used mixing method in industry, but sand milling is generally carried out in air, which is easy to cause excessive oxidation of the raw material ferrous sulfate during high-speed mixing. Summary of the invention
[0006] Therefore, the technical problem to be solved by the present invention is to at least partially overcome the defects of the prior art in which the dry process or the wet process is used to prepare the sodium ferric sulfate positive electrode material, such as the particles are loose at the microscopic level, the contact is not tight enough, and the wet process is difficult to achieve continuous large-scale production, thereby providing a carbon composite sodium ferric sulfate positive electrode material and its preparation method and application.
[0007] To this end, the present invention provides the following technical solutions.
[0008] The first aspect of the present invention provides a method for preparing a carbon composite sodium iron sulfate positive electrode material, comprising the following steps:
[0009] (1) mixing a carbon source, a sodium source, an iron source and a dispersant, and sand-milling to obtain a slurry; wherein the median particle size of the slurry is 220-450 nm;
[0010] (2) the slurry is subjected to suction filtration or pressure filtration to separate the solid and liquid to obtain a precursor;
[0011] (3) Sintering the precursor.
[0012] The method combines controlled wet mixing, suction filtration or pressure filtration, and solid-phase sintering, and controls the particle size of the slurry after sand grinding. When preparing a carbon composite sodium ferric sulfate positive electrode material, the raw materials are mixed evenly without looseness and other problems. The prepared composite sodium ferric sulfate positive electrode material has high particle density.
[0013] In some optional embodiments, the median particle size of the slurry is 220-450nm, which can be but not limited to 280nm, 290nm, 300nm, 330nm, 350nm, 370nm, 390nm, 400nm, 420nm, 440nm, etc. By controlling the median particle size to 220-450nm, the fineness of the slurry is small, the reaction activity between the iron source and the sodium source can be good, the raw materials react fully during the sintering process, and it is easier to form a pure phase. The slurry fineness is small, and the primary particles of the obtained material are small, which can shorten the transmission path of sodium ions in the material and further improve the electrochemical properties of the material; and controlling the median particle size of the slurry helps to improve the compactness of the positive electrode material particles, improve the contact of the raw materials during the sintering process, make it easier for molecules to diffuse during the reaction, reduce the generation of impurities, and further improve the compaction density of the material. It should be noted here that due to the influence of production equipment errors or detection equipment errors, the actual test results may have a deviation of ±20nm, so the median particle size is usually expressed as 220nm±20nm or 450nm±20nm.
[0014] In some optional embodiments, the vacuum degree of the filtration is not higher than 1×10 -3 Pa, for example, can be but not limited to 6×10 -4 Pa, 5×10 -4 Pa, 4×10 -4 Pa, 3×10 -4 Pa, 2×10 -4 Pa, 1×10 -4 Pa, 1×10 -5 Pa, 1×10 -6 Pa, etc.; by controlling the filtration pressure, the particle compactness of the material can be ensured to increase the compaction density.
[0015] In some optional embodiments, the pressure of the filter press is 0.4-1.2 MPa, such as but not limited to 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa, 1.0 MPa, 1.1 MPa, 1.2 MPa. By controlling the pressure of the filter press, the compactness of the particles in the material can be ensured to increase the compaction density.
[0016] In some optional embodiments, the holding time of suction filtration or pressure filtration is 2-5 hours, for example, but not limited to 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, etc. By controlling the holding time of suction filtration or pressure filtration, the pores between particles can be further shrunk, the compaction degree can be further improved, and the compaction density can be increased.
[0017] In some optional embodiments, when performing solid-liquid separation, the filter pore size of the filter plate is 0.2-0.5 μm, for example, the filter pore size can be but not limited to 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, etc. By controlling the filter pore size of the filter plate, it can be ensured that the ratio of the raw materials in the solid phase material after solid-liquid separation is the same as the original design ratio, thereby ensuring the performance of the positive electrode material. If the filter pore size is too large, part of the slurry will be drawn away, deviating from the original design ratio, and affecting the performance of the carbon composite sodium iron sulfate positive electrode material.
[0018] It should be noted here that during suction filtration or pressure filtration, the particles in the slurry agglomerate, and the particle size of the agglomerated particles is larger than the pore size of the filter plate, so there will be no problem of solid phase substances passing through the filter pores of the filter plate and being filtered out. The median particle size of the slurry is tested under ultrasonic conditions, which will destroy the agglomeration state and make the test results more accurate.
[0019] In some optional embodiments, the filtration is performed by isostatic pressing.
[0020] In some optional embodiments, the step of drying and dehydrating the sodium source and the iron source is further included before the sand milling. Preferably, the drying and dehydration is carried out under vacuum or nitrogen conditions, and the drying temperature is 80-110° C. The drying temperature can be but is not limited to 80° C., 85° C., 90° C., 95° C., 100° C., 105° C., 110° C., etc.
[0021] In some optional embodiments, the sodium source is sodium sulfate, and the iron source is ferrous sulfate heptahydrate.
[0022] In some optional embodiments, the step of adding an antioxidant inhibitor is further included before the sanding;
[0023] And / or, the antioxidant inhibitor is at least one of oxalic acid, sodium oxalate, ferrous oxalate and ascorbic acid.
[0024] And / or, the ratio of the total mass of the sodium source and the iron source after drying to the mass of the antioxidant inhibitor is 100:(0.1-10), for example, it can be but not limited to 100:0.5, 100:1.0, 100:2, 100:4, 100:6, 100:8, 100:8.5, 100:10, etc.
[0025] In some optional embodiments, the dispersant is an anhydrous dispersant;
[0026] and / or, the dispersant is at least one of methanol, ethanol, acetone, ether, isopropanol, acetonitrile, and N-methylpyrrolidone;
[0027] And / or, the ratio of the total mass of the sodium source after drying, the iron source and the carbon source after drying to the mass of the dispersant is (0.25-1):1, for example, it can be but not limited to 0.35:100, 0.45:100, 0.5:100, 0.6:100, 0.7:100, 0.8:100, 0.9:100, 1.0:100.
[0028] In some optional embodiments, when performing the sintering step, the heating rate is 1-5°C / min; for example, it can be but not limited to 2°C / min, 3°C / min, 4°C / min.
[0029] And / or, the sintering temperature is 300-400°C; for example, it can be but not limited to 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C.
[0030] And / or, the sintering time is 6-48 hours; for example, it can be but not limited to 7 hours, 10 hours, 13 hours, 16 hours, 19 hours, 22 hours, 25 hours, 28 hours, 31 hours, 34 hours, 37 hours, 40 hours, 45 hours. Preferably, the sintering is carried out in a nitrogen atmosphere.
[0031] In some optional embodiments, the molar ratio of iron in the iron source to sodium in the sodium source is (0.1-1.25):1; for example, it can be but not limited to 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.667:1, 0.8:1, 0.9:1, 1:1, 1.1:1, etc.
[0032] and / or, the carbon source is at least one of conductive carbon sp, carbon nanotubes, acetylene black, Ketjen black, graphene, and redox graphene;
[0033] And / or, the ratio of the total mass of the sodium source and the iron source after drying to the mass of the carbon source is 100:(2-10), for example, it can be but not limited to 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10.
[0034] In some optional embodiments, the step (3) further comprises a drying step before sintering. Preferably, the drying is carried out under vacuum or nitrogen conditions, and the drying temperature is 80-110° C. The drying temperature can be but is not limited to 80° C., 85° C., 90° C., 95° C., 100° C., 105° C., 110° C., etc.
[0035] A second aspect of the present invention provides a carbon composite sodium iron sulfate positive electrode material, which is prepared by the above method.
[0036] A third aspect of the present invention provides a battery, comprising the above-mentioned carbon composite sodium iron sulfate positive electrode material.
[0037] The technical solution of the present invention has the following advantages:
[0038] 1. The preparation method of the carbon composite sodium ferric sulfate positive electrode material provided by the present invention comprises: (1) mixing and sand-grinding a carbon source, a sodium source, an iron source and a dispersant to obtain a slurry; wherein the median particle size of the slurry is 220-450 nm; (2) the slurry is subjected to suction filtration or pressure filtration and solid-liquid separation to obtain a precursor; (3) the precursor is sintered. The method combines wet mixing, suction filtration or pressure filtration, and solid-phase sintering, and controls the median particle size of the slurry after sand grinding. When preparing the carbon composite sodium ferric sulfate positive electrode material, the raw materials are mixed evenly without problems such as looseness, and the obtained carbon composite sodium ferric sulfate positive electrode material has a high compaction density.
[0039] Controlling the median particle size of the slurry after sand grinding helps to improve the compactness of the positive electrode material particles, that is, the compaction density. It can also control the fineness of the slurry, thereby refining the particle size of the primary particles, improving the reaction activity of the raw materials, and obtaining a carbon-composite sodium iron sulfate positive electrode material with high phase purity; small primary particles can shorten the sodium ion transmission path and ensure the electrical properties of the positive electrode material.
[0040] The preparation method of the present invention does not require a sealed tank during the mixing process, and can achieve continuous large-scale production; the present invention performs solid-liquid separation by suction filtration or pressure filtration, which can achieve the recycling and reuse of the dispersant, does not involve the discharge of organic solvents, and overcomes the defects of the prior art wet process that is difficult to achieve continuous large-scale production and cannot control the generation of organic solvents during the production process. In addition, the carbon composite sodium iron sulfate cathode material prepared by the present invention has high capacity, excellent rate performance and cycle performance.
[0041] 2. The method for preparing the carbon composite sodium iron sulfate positive electrode material provided by the present invention further ensures the particle compactness of the material, that is, the compaction density, by controlling the vacuum degree of filtration or the pressure of pressure filtration, thereby preventing the problem of looseness due to too low pressure.
[0042] 3. The preparation method of the carbon composite sodium iron sulfate positive electrode material provided by the present invention can further shrink the pores between the particles and further improve the compaction density by controlling the holding time of suction filtration or pressure filtration. Low holding time and pressure will result in (1) insufficient reaction; (2) poor contact between the sodium source, iron source and carbon source, which can easily interrupt the conductive network, thereby affecting the electrical properties of the material and the compaction density.
[0043] 4. The preparation method of the carbon composite sodium iron sulfate positive electrode material provided by the present invention can make the ratio of raw materials in the solid phase material after solid-liquid separation the same as the original design ratio by controlling the pore size of the filter plate, thereby ensuring the performance of the positive electrode material. When the pore size of the filter plate is too large, part of the slurry is drawn away during the suction filtration or pressure filtration process, deviating from the original design ratio and affecting the performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0045] Figure 1 is a SEM image of the carbon composite sodium iron sulfate positive electrode material prepared in Example 5 of the present invention;
[0046] Figure 2 is a cycle performance curve diagram of the carbon composite sodium iron sulfate positive electrode material prepared in Example 5 of the present invention;
[0047] Figure 3 is the powder compaction density of the carbon composite sodium iron sulfate positive electrode material prepared in Example 5 of the present invention under different pressures;
[0048] Figure 4 It is the XRD diffraction pattern of the positive electrode materials of Examples 1, 2, 5, 6, 7 of the present invention and Comparative Examples 1 and 4. DETAILED DESCRIPTION
[0049] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0050] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0051] Preparation of test materials
[0052] Preparation Example 1
[0053] This preparation example provides a method for preparing a carbon composite sodium iron sulfate positive electrode material, comprising the following steps:
[0054] (1) According to the Fe:Na molar ratio of 1:1, 10080g of ferrous sulfate heptahydrate and 2570g of sodium sulfate were weighed, placed in an oven, dried and dehydrated at 105°C for 24h, and set aside. Among them, the mass of ferrous sulfate after drying is about 54wt% of that before drying, and the mass of other raw materials before and after drying is basically unchanged.
[0055] (2) Weigh 400 g of carbon nanotubes and 400 g of anhydrous oxalic acid, mix them with the ferrous sulfate and sodium sulfate dried and dehydrated in step (1), add 9000 g of methanol for sand grinding, at this time, the mass ratio of the total mass of the dried sodium sulfate and ferrous sulfate to the carbon nanotubes is 100:5; the mass ratio of the total mass of the dried sodium sulfate and ferrous sulfate to the antioxidant inhibitor anhydrous oxalic acid is 100:5; the ratio of the total mass of the dried sodium sulfate, the dried ferrous sulfate and the carbon nanotubes to the mass of the dispersant methanol is 0.9348:1, and the median particle size D50 of the slurry after sand grinding is 281 nm±20 nm.
[0056] Preparation Example 2
[0057] This preparation example provides a method for preparing a carbon composite sodium iron sulfate positive electrode material, comprising the following steps:
[0058] (1) According to the Fe:Na molar ratio of 0.7:1, 4430 g of ferrous sulfate heptahydrate and 1620 g of sodium sulfate were weighed, placed in an oven, dried and dehydrated at 100°C for 24 h, and set aside.
[0059] (2) Weigh 120 g of carbon nanotubes and 150 g of ascorbic acid, mix them with the ferrous sulfate and sodium sulfate dried and dehydrated in step (1), add 4500 g of N-methylpyrrolidone for sand grinding, at this time, the mass ratio of the total mass of the dried sodium sulfate and ferrous sulfate to the carbon nanotubes is 100:2.99; the mass ratio of the total mass of the dried sodium sulfate and ferrous sulfate to the antioxidant inhibitor ascorbic acid is 100:3.74; the ratio of the total mass of the dried sodium sulfate, the dried ferrous sulfate and the carbon nanotubes to the mass of the dispersant N-methylpyrrolidone is 0.92:1, and the median particle size D50 of the slurry after sand grinding is 320 nm±20 nm.
[0060] Preparation Example 3
[0061] This preparation example provides a method for preparing a carbon composite sodium iron sulfate positive electrode material, comprising the following steps:
[0062] (1) According to the Fe:Na molar ratio of 0.667:1, 4350 g of ferrous sulfate heptahydrate and 1670 g of sodium sulfate were weighed, placed in an oven, dried and dehydrated at 110°C for 24 h, and set aside.
[0063] (2) Weigh 200 g of carbon nanotubes and 250 g of ascorbic acid, mix them with the ferrous sulfate and sodium sulfate dried and dehydrated in step (1), add 6400 g of anhydrous ethanol and sand grind them. At this time, the mass ratio of the total mass of the dried sodium sulfate and ferrous sulfate to the carbon nanotubes is 100:4.98; the mass ratio of the total mass of the dried sodium sulfate and ferrous sulfate to the antioxidant inhibitor ascorbic acid is 100:6.22; the ratio of the total mass of the dried sodium sulfate, the dried ferrous sulfate and the carbon nanotubes to the mass of the dispersant anhydrous ethanol is 0.66:1, and the median particle size D50 of the slurry after sand grinding is 442 nm±20 nm.
[0064] Preparation Example 4
[0065] The basic contents of this preparation example are the same as those of Preparation Example 3, except that the median particle size D50 of the slurry after sand grinding is 249 nm ± 20 nm.
[0066] Preparation Example 5
[0067] The basic contents of this preparation example are the same as those of Preparation Example 3, except that the median particle size D50 of the slurry after sand grinding is 290 nm ± 20 nm.
[0068] Preparation Example 6
[0069] The basic contents of this preparation example are the same as those of Preparation Example 3, except that no dispersant is used in the sand milling, and the median particle size D50 of the slurry after sand milling is 282 nm ± 20 nm.
[0070] Preparation Example 7
[0071] The basic content of this preparation example is the same as that of Preparation Example 3, except that the median particle size D50 of the slurry after sand grinding is 500nm±20nm.
[0072] Preparation Example 8
[0073] The basic contents of this preparation example are the same as those of Preparation Example 3, except that the median particle size D50 of the slurry after sand grinding is 150 nm ± 20 nm.
[0074] Example 1
[0075] This example uses the slurry prepared in Preparation Example 1 for further processing:
[0076] (1) The slurry is filtered under negative pressure, and the filtration pressure is 6×10 -4 Pa, the pressure holding time is 3h, the pore size of the filter plate is 0.3μm, and the filtrate is collected for next reuse; the filter cake is placed in a vacuum oven and dried at 105℃ for 24h.
[0077] (2) The dried filter cake was placed in a nitrogen atmosphere, heated to 350° C. at a heating rate of 2° C. / min, and then sintered for 12 h to obtain a carbon composite sodium iron sulfate positive electrode material.
[0078] Example 2
[0079] This example uses the slurry prepared in Preparation Example 2 for further processing:
[0080] (1) The slurry is filtered at a pressure of 0.6 MPa, a pressure holding time of 2 h, a filter plate pore size of 0.4 μm, and the filtrate is collected for next reuse; the filter cake is placed in a vacuum oven and dried at 100° C. for 24 h.
[0081] (2) The dried filter cake was placed in a nitrogen atmosphere, heated to 360° C. at a heating rate of 3° C. / min, and then sintered for 10 h to obtain a carbon composite sodium iron sulfate positive electrode material.
[0082] Example 3
[0083] This example uses the slurry prepared in Preparation Example 3 for further processing:
[0084] (1) The slurry is filtered at a pressure of 1.2 MPa, the pressure holding time is 5 h, the filter plate pore size is 0.5 μm, and the filtrate is collected for reuse next time; the filter cake is placed in a vacuum oven and dried at 110° C. for 24 h.
[0085] (2) The dried filter cake was placed in a nitrogen atmosphere, heated to 355° C. at a heating rate of 2° C. / min, and then sintered for 12 h to obtain a carbon composite sodium iron sulfate positive electrode material.
[0086] Example 4
[0087] This example uses the slurry prepared in Preparation Example 4 for further processing. The other differences from Example 3 are: the filtration pressure is 0.4 MPa, the pressure holding time is 2 h, and the filter plate pore size is 0.2 μm.
[0088] Example 5
[0089] This example uses the slurry prepared in Preparation Example 5 for further processing. The other differences from Example 3 are: the filtration pressure is 1.0 MPa, the pressure holding time is 3 hours, and the filter plate pore size is 0.3 μm.
[0090] Example 6
[0091] This example uses the slurry prepared in Preparation Example 5 for further processing. The other differences from Example 5 are: the pressure holding time is 0.5h, and the pore size of the filter plate is 1.0μm.
[0092] Example 7
[0093] This example uses the slurry prepared in Preparation Example 5 for further processing, and the other differences from Example 5 are: the pore size of the filter plate is 1.0 μm.
[0094] Example 8
[0095] This embodiment uses the slurry prepared in Preparation Example 5 for further processing, and the other contents are different from Example 5 in that the pore size of the filter plate is 0.1 μm.
[0096] Example 9
[0097] This example uses the slurry prepared in Preparation Example 5 for further processing, and the other differences from Example 5 are: the pressure of the filtration is 0.3 MPa.
[0098] Example 10
[0099] This example uses the slurry prepared in Preparation Example 5 for further processing, and the other differences from Example 5 are: the pressure of the filtration is 1.3 MPa.
[0100] Embodiment 11
[0101] This example uses the slurry prepared in Preparation Example 5 for further treatment. The other differences from Example 1 are as follows: the filtration pressure is 5×10 -4 Pa.
[0102] Example 12
[0103] This embodiment uses the slurry prepared in Preparation Example 5 for further processing, and the other differences from Example 5 are: the pressure holding time is 6 hours.
[0104] Example 13
[0105] This embodiment uses the slurry prepared in Preparation Example 5 for further processing, and the other differences from Example 5 are: the pressure holding time is 1 hour.
[0106] Embodiment 14
[0107] This embodiment uses the slurry prepared in Preparation Example 1 for further processing, and the other differences from Example 1 are: the pressure holding time is 2 hours.
[0108] Embodiment 15
[0109] This embodiment uses the slurry prepared in Preparation Example 1 for further processing, and the other differences from Example 1 are: the pressure holding time is 5 hours.
[0110] Example 16
[0111] This embodiment uses the slurry prepared in Preparation Example 1 for further processing, and the other differences from Example 1 are: the pressure holding time is 4 hours.
[0112] Embodiment 17
[0113] This example uses the slurry prepared in Preparation Example 1 for further processing, and the other differences from Example 1 are: the pore size of the filter plate is 1.0 μm.
[0114] Comparative Example 1
[0115] In this comparative example, the slurry prepared in Preparation Example 7 was further processed, that is, the median particle size of the slurry after sand grinding was 500nm±20nm, and the other contents were basically the same as those in Example 5.
[0116] Comparative Example 2
[0117] In this comparative example, the slurry prepared in Preparation Example 8 was further processed, that is, the median particle size of the slurry after sand grinding was 150nm±20nm, and the other contents were basically consistent with Example 5.
[0118] Comparative Example 3
[0119] In this comparative example, the slurry prepared in Preparation Example 6 was further processed, that is, the median particle size of the slurry after sand grinding was 282 nm ± 20 nm, the slurry did not contain a dispersant, and the other contents were basically the same as those in Example 5.
[0120] Comparative Example 4
[0121] This comparative example uses the slurry prepared in Preparation Example 5 for further processing, that is, the median particle size of the slurry after sand grinding is 290nm±20nm. The difference from Example 5 is that spray drying is directly performed without filter pressing, and then sintering is performed.
[0122] Table 1 Key parameters in the examples and comparative examples
[0123]
[0124]
[0125] Note: “ / ” in the table means no dispersant was added.
[0126] Test example
[0127] This test example provides the performance test and results of the positive electrode materials obtained in the above examples and comparative examples:
[0128] (1) The carbon composite sodium iron sulfate positive electrode material provided in each embodiment and comparative example is made into a button half-cell for electrical performance testing. Among them, the preparation method of the button cell comprises: the positive electrode material obtained in the embodiment and comparative example, conductive carbon black (super P), and PVDF are mixed and dissolved in NMP in a mass ratio of 96:2:2, and after being fully stirred, the positive electrode sheet is coated on the aluminum foil using an automatic coating machine, and the coated electrode sheet is dried at 105°C in vacuum for 12 hours, and then rolled by a roller press. The rolled positive electrode sheet is cut into a disc with a diameter of 12 mm, and the metal sodium is used as the negative electrode sheet, the glass fiber membrane is used as the diaphragm, and the electrolyte is 1MmolNaPF6 dissolved in EC:DEC=1:1 organic electrolyte. The CR2032 button cell is assembled in an argon-protected glove box, and the 1C current of the battery charge and discharge is 120mA / g. The battery performance is tested, and the results are shown in Table 2.
[0129] The powder compaction density was obtained by using a powder compaction density meter. The results are shown in Table 2.
[0130] Table 2 Performance test results of positive electrode materials and corresponding batteries in various embodiments and comparative examples
[0131]
[0132]
[0133] Table 2 shows the positive electrode materials and corresponding battery performance test results of various embodiments and comparative examples, including discharge capacity, cycle performance, carbon content design, and compaction density of carbon composite sodium iron sulfate positive electrode materials. From the results of Examples 1-3 in Table 2, different sodium-iron ratios have little effect on the discharge capacity and cycle performance of the positive electrode materials, and also have little effect on the compaction density and carbon content of the carbon composite sodium iron sulfate materials.
[0134] From the results of Examples 1, 5, 7-8, and 17, controlling the pore size of the filter plate at 0.2-0.5 μm helps to make the raw material ratio in the positive electrode material the same as the original design, and further improves the discharge capacity and capacity retention rate of the positive electrode material, thereby ensuring the performance of the positive electrode material. From the results of Examples 6-7, when the holding time is controlled at 3 hours, it helps to keep the carbon content in the product consistent with the original design, and improve the compaction density, indicating that controlling the holding time at 2-5 hours helps to improve the compaction density. From Examples 9-10, the filtration pressure will affect the compaction density and electrical properties of the material. When the pressure of the filter press is preferably 0.4-1.2 MPa, it will help to further improve the electrical properties of the battery. Too low a pressure of the filter press will affect the compaction density of the positive electrode material. From Examples 12-13, when performing filter press, the holding time will affect the discharge capacity of the battery and the compaction density of the carbon composite sodium ferric sulfate material.
[0135] (2) Figure 1 is a SEM image of the carbon composite sodium iron sulfate positive electrode material obtained in Example 5. Figure 1 It can be seen that the primary particles of the material are in close contact, and the CNTs are evenly dispersed between the particles, forming a good conductive network and improving the material rate performance.
[0136] Figure 2 : is a cycle performance curve of the carbon composite sodium iron sulfate positive electrode material prepared in Example 5. Figure 2 It can be seen that the initial gram capacity of the positive electrode material at 1C discharge is about 91 mAh / g, the gram capacity after 200 cycles of discharge is about 84.4 mAh / g, and the capacity retention rate after 200 cycles of 1C charge and discharge is 92.7%.
[0137] Figure 3 is the powder compaction density of the carbon composite sodium iron sulfate positive electrode material obtained in Example 5 under different pressures, from Figure 3 It can be seen that the precursor particles obtained by the filter press process are in close contact with each other, with fewer gaps between particles, and the material obtained after sintering has a high compaction density.
[0138] (3) Figure 4 It is the XRD diffraction pattern of the positive electrode materials of Examples 1, 2, 5, 6, 7 and Comparative Examples 1 and 4. Figure 4 It can be seen that after the pore size of the filter plates in Examples 6 and 7 becomes larger, the inventors found that the filtrate after filtration is black during the experiment, indicating that some components are drawn away with the filtrate, deviating from the original design ratio, and some small impurity peaks appear on the XRD spectrum, affecting the electrical properties of the material. In Comparative Example 1, the median particle size of the slurry becomes relatively larger after sand milling, and the components are prone to uneven mixing. In addition, the particles are too large, and the raw material reactivity is low, resulting in the generation of impurities, which in turn affects the electrical properties, resulting in a decrease in discharge capacity and cycle retention rate. Comparative Example 4 adopts a spray drying method, and the raw material particles in the obtained precursor have poor contact, low reactivity, and impurities, which reduces the electrical properties.
[0139] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A method for preparing a carbon composite sodium iron sulfate positive electrode material, characterized in that: The following steps are involved: (1) mixing a carbon source, a sodium source, an iron source and a dispersant, and sand-milling to obtain a slurry; wherein the median particle size of the slurry is 220-450 nm; (2) The slurry is filtered or pressed to separate the solid and liquid to obtain a precursor; (3) sintering the precursor; The vacuum degree of the filtration is not higher than 1×10 -3 Pa, the pressure holding time is 2-5h; or, The pressure of the filter press is 0.4-1.2 MPa, and the pressure holding time is 2-5 hours.
2. The preparation method according to claim 1, characterized in that: The filtration is performed by isostatic pressing.
3. The preparation method according to claim 1, characterized in that: When performing the solid-liquid separation, the pore size of the filter plate is 0.2-0.5 μm.
4. The preparation method according to claim 1, characterized in that: The molar ratio of the iron in the iron source to the sodium in the sodium source is (0.1-1.25):1; and / or, the carbon source is at least one of conductive carbon, carbon nanotubes, acetylene black, Ketjen black, graphene and redox graphene; And / or, the ratio of the total mass of the sodium source and the iron source after drying to the mass of the carbon source is 100:(2-10).
5. The preparation method according to claim 1, characterized in that: The step (1) further comprises the step of adding an antioxidant inhibitor before the sand grinding.
6. The preparation method according to claim 5, characterized in that: The antioxidant inhibitor is at least one of oxalic acid, sodium oxalate, ferrous oxalate and ascorbic acid.
7. The preparation method according to claim 5, characterized in that: The ratio of the total mass of the sodium source and the iron source after drying to the mass of the antioxidant inhibitor is 100:(0.1-10).
8. The preparation method according to claim 1, characterized in that: The dispersant is an anhydrous dispersant.
9. The preparation method according to claim 1, characterized in that: The dispersant is at least one of methanol, ethanol, acetone, ether, isopropanol, acetonitrile and N-methylpyrrolidone.
10. The preparation method according to claim 1, characterized in that: The ratio of the total mass of the dried sodium source, the dried iron source and the carbon source to the mass of the dispersant is (0.25-1):
1.
11. A carbon composite sodium iron sulfate positive electrode material, characterized in that: The method is prepared according to any one of claims 1 to 10.
12. A battery, characterized in that: It comprises the carbon composite sodium ferric sulfate positive electrode material prepared by the preparation method according to any one of claims 1 to 10 or the carbon composite sodium ferric sulfate positive electrode material according to claim 11.
Citation Information
Patent Citations
Preparation method of high-density lithium iron phosphate cathode material
CN108529584A
Sodium-ion battery positive electrode material as well as preparation method and application thereof
CN115064676A
Preparation method of sodium ferrous sulfate / carbon composite positive electrode material, positive electrode material, positive electrode plate and sodium ion battery
CN117154062A
Sodium ferric sulfate positive electrode material and synthesis method thereof
CN117585723A